Optimization of the culture media for protease production by phytopathogenic fungus Fusarium graminearum and characterization of the enzyme - Abaildayev, A.O.; Kuzovlev, V.A.; Khakimzhanov А.А. (Fundamental and Experimental Biology, 2022)
One of the modern directions of increasing the resistance of cereal crops to fungal diseases is the study of hydrolytic digestive enzymes of pathogens and their protein inhibitors in grain. In this study, the optimal nutrient media for obtaining the protease of the phytopathogenic fungus Fusarium graminearum containing 1 % of glucose and 1 % of yeast extract as an inducer of enzyme synthesis is determined. The cultivation period of the fungus with the inoculation of 3.8 x 106 conidia / 100 ml is 12–14 days, at which the synthesis of protease is maximum. By affinity (biospecific) chromatography, extracellular serine trypsinlike protease is purified from the accumulated preparative amount of cultural filtrate, represented by two proteins with MW-24 and 27-kDa according to SDS electrophoresis data. The main physicochemical properties of the enzyme im-portant for its activity and interaction with protein inhibitors — pH and temperature optima, thermal stability, sensitivity to metal ions, are established. These characteristics for the trypsin protease of F. graminearum are given for the first time. The study results can be used in the search for specific protease inhibitors in grain as protective proteins for their use in assessing the resistance of wheat varieties to fungal attacks.